How you get it matters: Moderating role of transfer method in guiding ownership assignments for modified objects - Li, Zhanxing; Dong, Dong (Frontiers in Psychology, 2023)
Previous research has found that value change and creation drive people to support the laborer more than the original owner in ownership reasoning for modified objects; however, the transfer methods used to resolve conflicts have largely been ignored. In this work, two studies were designed to investigate the role of value change and creation in adults’ labor-based ownership judgments in four transfer conditions (i.e., take/steal/borrow/find). The results indicated that people were more likely to assign ownership to the original owner in the take, steal and borrow conditions but not in the find condition, and this reasoning held regardless of whether the original materials showed high or low value appreciation or successful creation, and it was applicable to raw materials with low (Study 1) and high values (Study 2). The results suggest that the transfer method is more important than the value change or creation status in guiding people’s ownership assignments. These findings provide insights for real-life mediation of ownership conflicts.